Roles of the Sec2p Gene in the Growth and Pathogenicity Regulation of Aspergillus fumigatus - Yuhuan Liu; Shumi Shang; Cong Liu; Yichen Liu; Keyang Xu; Dan He; Li Wang (Journal of Fungi)
Aspergillus fumigatus (A. fumigatus) is a filamentous fungus that causes invasive aspergillosis in immunocompromised individuals. Regulating fungal growth is crucial for preventing disease development. This study found that deleting the guanine nucleotide exchange factor Sec2p gene led to slower A. fumigatus growth and reduced the fungal burden and mortality of infected mice. However, the mechanism by which this gene affects A. fumigatus growth and pathogenicity remains unclear. Transmission electron microscopy revealed that the vacuoles of the gene knockout strain ΔSec2p accumulated more autophagosomes, indicating inhibition of autophagosome degradation. When phenylmethylsulfonyl fluoride was applied to inhibit autophagosome degradation, the ΔSec2p strain produced fewer autophagosomes; the ΔSec2p autophagy pathway was inhibited, affecting A. fumigatus’ nutrient homeostasis and growth. Unlike the wild type, the ΔSec2p strain showed strong resistance to cell wall stress. When exposed to caspofungin, Sec2p negatively regulated the expression of cell wall integrity (CWI) pathway genes and participated in the cell wall stress response of A. fumigatus. Furthermore, this gene positively regulated the autophagy pathway and enhanced CWI pathway gene expression to respond to rapamycin-induced autophagy. In summary, Sec2p positively regulated the autophagy pathway; it negatively regulated the CWI pathway during cell wall stress, coordinating the growth and pathogenicity of A. fumigatus.